Human resource development - Werner, Jon M. (Thomson South-Western, 2006)
Covers the field of HRD from orientation and skills training, to career and organizational development. This book shows how concepts and theory can and have been put into practice in a variety of organizations. It focuses on the shared role of line management and human resource specialists in HRD and offers real-world practices